Wish I Were Here - Kingwell, Mark (Tantor Media, Inc., 2019)
Are you bored of the endless scroll of your social media feed? Do you swipe left before considering the human being whose face you just summarily rejected? Do you skim articles on your screen in search of intellectual stimulation that never arrives? If so, this book is the philosophical lifeline you have been waiting for. Offering a timely meditation on the profound effects of constant immersion in technology, also known as the Interface, Wish I Were Here draws on philosophical analysis of boredom and happiness to examine the pressing issues of screen addiction and the lure of online outrage. Without moralizing, Mark Kingwell takes seriously the possibility that current conditions of life and connection are creating hollowed-out human selves, divorced from their own external world. While scrolling, swiping, and clicking suggest purposeful action, such as choosing and connecting with others, Kingwell argues that repeated flicks of the finger provide merely the shadow of meaning, by reducing us to scattered data fragments, Twitter feeds, Instagram posts, shopping preferences, and text trends captured by algorithms. Written in accessible language that references both classical philosophers and contemporary critics, Wish I Were Here turns to philosophy for a cure to the widespread unease that something is amiss in modern waking life.
Online resource; Title from title page (viewed April 30, 2019)
Keywords: Technology -- Philosophy; Technologie; Philosophie; Technology; Philosophy; Downloadable audio books; Audiobooks; Livres audio